The Impact of Dental Anxiety on the State of Oral Hygiene in Children - Ortikova Nargiza Khairullayevna (Genius Journals, 2023)
Dental anxiety plays a major role in the behavior of children at outpatient dental appointments. Not every dentist can work with children, and it's not only and not so much about permits. Children are a special category of patients; accordingly, they need a special approach. Someone can quickly find a common language with young patients, someone can't. A visit to the dentist can easily cause a strong fear reaction and acute anxiety in children. This is one of the most basic reasons for avoiding and neglecting dental care. This may interfere with the provision of dental care, as the child may not want to take the treatment provided by the dentist
Keywords: dental anxiety; anxiety; neuropsychological tests